The Worlds Best Class Plant - Scanlon, Liz Garton; Vernick, Audrey; Bontigao, Lynnor (New York : G. P. Putnams Sons, 2023)
A class that is terribly disappointed in their lack of a class pet discovers that having a class plant is the best thing ever.
Ages 3-7.
Keywords: Plants -- Juvenile fiction; Schools -- Juvenile fiction; Pets -- Juvenile fiction; Plants -- Fiction; Schools -- Fiction; Pets -- Fiction; Picture books